Traditional Vrikshayurveda practices yielded equally to modern scientific agricultural practices in Proso millet (Panicum miliaceum L.) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Ancient India adopted many traditional practices to maintain soil health and therefore crop yields and, one such facet is “Vrikshayurveda”; meantime, post green revolution era followed scientific conventional practices, which enhanced crop yields, at loss of soil health. It is the time to evaluate ancient organic practices for chemical free food production. Millets are rich in nutrients and sustaining more than 30% of world’s population. Proso millet, a versatile crop capable of adapting to varied environments from tropics to temperate, is rich in nutrients. As there is little information available on evaluation of such practices in crops like millets, we conducted this study to evaluate field performance of proso millet under Vrikshayurveda practices in comparison with modern crop production practices and do-nothing practice. Laboratory and field research were carried out at Agricultural College and Research Institute, Tamil Nadu Agricultural University, Madurai during 2020-21. Treatments include; Biomass Transfer (BMT) from five trees viz., Albizia lebbek (L.) Benth, Delonix regia Boj.ex Hook., Gliricidia sepium (Jacq.) Steud, Peltophorum ferrugineum (Decne.) Benth and Pongamia pinnata (L.) Pierre and Leaf Tea spray of extracts from five tree species viz., Morinda tinctoria Roxb., Moringa oleifera Lam., Mangifera indica (L.), Annona squamosa (L.) and Aegle marmellos (L.) Correa. Study revealed that agrochemical-free, high-quality foodgrains in proso millet is achievable by adopting Vrikshayurveda practice of soil enrichment with BMT of Albizia lebbek and Gliricidia sepium on nitrogen equivalent basis and leaf tea spray (LTS) viz., Mangifera indica and Moringa oleifera at 5% resulted in